2016
DOI: 10.1016/j.jtcme.2014.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Antcin K, an active triterpenoid from the fruiting bodies of basswood cultivated Antrodia cinnamomea, induces mitochondria and endoplasmic reticulum stress-mediated apoptosis in human hepatoma cells

Abstract: Liver cancer is the second leading cause of cancer deaths in Taiwan as per the 2011 statistics and ranks fourth in cancer-related mortality in the world. Recent researches have shown that Antrodia cinnamomea, a Taiwan-specific medicinal mushroom, has biological activities, including hepatoprotection, anti-inflammation, antihepatitis B virus activity, and anticancer activity. In the present study, the antiproliferative activity and molecular mechanisms of antcin K, the most abundant ergostane triterpenoid from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Annexin V is one of the calcium-binding protein located on the inner cell membrane, and it is inverted into the outer membrane after apoptosis induction. 25 Our results demonstrate that 37.5 and 50 μg/mL MHA treatment induced annexin V protein overexpression in SUP-T1 lymphoma cells. Figure 4 presents clearly apoptotic circumstances after MHA treatment for 24 hr in human lymphoma cells.…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…Annexin V is one of the calcium-binding protein located on the inner cell membrane, and it is inverted into the outer membrane after apoptosis induction. 25 Our results demonstrate that 37.5 and 50 μg/mL MHA treatment induced annexin V protein overexpression in SUP-T1 lymphoma cells. Figure 4 presents clearly apoptotic circumstances after MHA treatment for 24 hr in human lymphoma cells.…”
Section: Resultsmentioning
confidence: 50%
“…In order to investigate MHA induce apoptosis in SUP‐T1 lymphoma cells, the annexin V‐FITC protein expression was detected by flow cytometry. Annexin V is one of the calcium‐binding protein located on the inner cell membrane, and it is inverted into the outer membrane after apoptosis induction . Our results demonstrate that 37.5 and 50 μg/mL MHA treatment induced annexin V protein overexpression in SUP‐T1 lymphoma cells.…”
Section: Resultsmentioning
confidence: 66%
“…The anti-cancer properties of A. cinnamomea have been attributed to its unique composition of phytochemicals such as antroquinonols, antcins, and antrodins [12-15, 23, 24]. Among them, the antcins (ATA, antcin-B, antcin-C, antcin-D, antcin-E, antcin-F, antcin-G, antcin-H, antcin-I, antcin-K, and antcin M) are steroid-like compounds that exert various biological activities including, anti-inflammation [16,25], hepatoprotection [26][27][28], anti-aging [29], anti-cancer [30][31][32][33], and anti-metastasis [34]. We have previously reported that ATA isolated from the fruiting bodies of A. cinnamomea inhibits inflammation in lung cells via mimicking a glucocorticoid receptor agonist, and this effect was highly comparable with synthetic steroids, such as cortisone and dexamethasone [16].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the abundance of antcin K in wood-cultivated, as well as in dish-cultivated, A. cinnamomea, many bioactivities of antcin K have been found [3][4][5][6][7][8]. In contrast, few studies on antcamphin E and antcamphin F have been reported, due to their rarity.…”
Section: Discussionmentioning
confidence: 99%